# Y=x^2-6x+8 in to the form y=a(x-h)^2+k

Y=x^2-6x+8 in to the form y=a(x-h)^2+k

How do you change the function?

This initial problem is followed by:

a) What is the equation for the line of symmetry for the graph of the function.

(I think I can solve this )

Please explain and show in detail how to break this down in (dummy language)

b) Asks that the function be graphed based on the initial form of y=a(x-h)^2+k

I know how to graph it once I can solve it.) Why do you not have to plot points when using:

y=a(x-h)^2+k

And note how this graph compares to the graph of y=x^2